2005
DOI: 10.1103/physreva.71.061802
|View full text |Cite
|
Sign up to set email alerts
|

Optical third-harmonic generation using ultrashort laser pulses

Abstract: To better predict optical third-harmonic generation ͑THG͒ in transparent dielectrics, we model a typical ultrashort pulsed Gaussian beam, including both group velocity mismatch and phase mismatch of the fundamental and harmonic fields. We find that competition between the group velocity mismatch and phase mismatch leads to third-harmonic generation that is sensitive only to interfaces. In this case, the spatial resolution is determined by the group velocity walk-off length. THG of modern femtosecond lasers in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
20
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 12 publications
0
20
0
Order By: Relevance
“…This unbalances the TH generated at the entrance and exit interfaces. Other authors also observed such asymmetry [11,12], but none of them considered self-focusing of light for its explanation.To fully understand the results presented later, we consider the usual THG cubic dependence on the fundamental beam irradiance [13], which depends on the beam waist radius: …”
mentioning
confidence: 89%
See 1 more Smart Citation
“…This unbalances the TH generated at the entrance and exit interfaces. Other authors also observed such asymmetry [11,12], but none of them considered self-focusing of light for its explanation.To fully understand the results presented later, we consider the usual THG cubic dependence on the fundamental beam irradiance [13], which depends on the beam waist radius: …”
mentioning
confidence: 89%
“…This unbalances the TH generated at the entrance and exit interfaces. Other authors also observed such asymmetry [11,12], but none of them considered self-focusing of light for its explanation.…”
mentioning
confidence: 89%
“…The probe pulse induces an oscillating polarization density at ω 3 3ω 1 and generates a TH pulse [26][27][28][29]:…”
Section: Third Harmonic Generation and Propagationmentioning
confidence: 99%
“…This is in contrast to other processes such as degenerate four-wave mixing and optical Kerr effect [23], where other competing nonlinear effects complicate the experimental analysis. THG has been observed in several materials including: BIBO (Bismuth triborate, 6 3 O BiB ) [24], thin sapphire crystals [25], fused silica [26], carbon nanotubes [27], and other types of single crystals [28].…”
mentioning
confidence: 99%